Estimating recent forest losses in Bosnia and Herzegovina by using the Copernicus and Corine land cover databases : Procjena recentnih gubitaka šume u Bosni i Hercegovini korištenjem Copernicus i Corine land cover baze podataka - Drašković, Branislav (Array, 2021)
The analysis of data from the first two decades of the 21st century shows that the area under forests in Bosnia and Herzegovina is gradually decreasing. In order to gain a detailed insight into this process, the paper will analyse the forest databases of the European satellite monitoring program Copernicus. This program, among other things, monitors the condition of forests in 39 European countries by using the High Resolution Layer (HRL). The HRL Forests database consists of 3 types of (status) products, and additional change products. The status products are available for the reference years 2012, 2015, and 2018. The status layers provide information on the Dominant Leaf Type and the Tree Cover Density at pixel level for the reference year 2018 in 10 m resolution. The Forest Type layer largely follows the Food and Agriculture Organization (FAO) forest definition. Also, the paper will use the data on forests from the CORINE Land Cover project for 2000, 2006, 2012 and 2018. The time-series includes a land change layer, highlighting changes in land cover and land use. The CLC Changes database will be analysed separately for three periods: 2000-2006, 2006-2012 and 2012-2018, due to more accurate data on forest losses. The results of the research show that forests in Bosnia and Herzegovina were reduced by 2.95%, in the period 2012-2018, where 2.55% of them were coniferous. Forests are primarily endangered by the process of conversion to transitional forest / shrub and fires.